2021
DOI: 10.1021/acsomega.1c04266
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Assessment of Rottlerin from Mallotus philippensis Using a Highly Sensitive Liquid Chromatography–Tandem Mass Spectrometry-Based Bioanalytical Method

Abstract: Rottlerin is a key bioactive phytoconstituent present in the pericarp of Mallotus philippensis. It shows promising multifaceted pharmacological actions against cancer. However, there is hardly any report for the quantification of rottlerin in the biological matrix and on its pharmacokinetic behavior. Therefore, we aimed in the present study to assess selective in vitro ADME properties and in vivo pharmacokinetics of isolated and characterized rottlerin using a newly developed and validated liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…The whole blood stability of the HA-ss-TAC conjugate was assessed in rat blood using a previously reported protocol. , Fresh whole blood was obtained from control Wistar rats in our institutional animal house. A stock solution of HA-ss-TAC conjugate was prepared in a solvent mixture of DMSO and water: (20:80, % v/v).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The whole blood stability of the HA-ss-TAC conjugate was assessed in rat blood using a previously reported protocol. , Fresh whole blood was obtained from control Wistar rats in our institutional animal house. A stock solution of HA-ss-TAC conjugate was prepared in a solvent mixture of DMSO and water: (20:80, % v/v).…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic stability study of TAC and its conjugate was performed in human liver microsomes (HLM) using our earlier reported protocol . The stock solutions of TAC or its conjugate were prepared in DMSO or 20% DMSO + 80% water (v/v), respectively, and diluted further with acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic stability study of 12a and 13 was performed in HLM and RLM using our earlier reported protocol (Dogra, Kotwal, et al, 2020; Manhas et al, 2021; M. Sharma et al, 2022). The incubation of test compounds with microsomal proteins was done with and without the presence of NADPH at 0, 15, and 30 min time points.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic stability study of 12a and 13 was performed in HLM and RLM using our earlier reported protocol Manhas et al, 2021;M. Sharma et al, 2022).…”
Section: Metabolic Stability Of 12a and 13 (In Vitro)mentioning
confidence: 99%